TOURISM AND EDUCATIONAL PROGRESS: ENHANCING SCHOOLS AND UNIVERSITIES IN MADAGASCAR - Eric, Ralainirina Razokiny; Arrive, Tsitaire Jean; Emynorane, Ralaivao Hanginiaina (YAYASAN CENDEKIA CITRA GEMILANG, 2025)
Tourism has become an important sector in Madagascar, with growing potential to generate income, create jobs, and foster international exchange. However, its contribution to the country's education system remains underexplored. This study investigates the ways in which tourism interacts with schools and universities, focusing on its impact on infrastructure, teacher capacity, student opportunities, and community perceptions. A qualitative research design is employed, combining direct observation and semi-structured interviews with 30 purposively selected informants, including school directors, teachers, university lecturers, students, parents, tourism operators, and local leaders. Data are analyzed thematically to identify key patterns and cross-validated through triangulation to ensure credibility. Findings reveal that tourism's influence on education in Madagascar is still modest and uneven. Some schools located near tourist destinations benefit from occasional donations or NGO-led projects, but most institutions lack systematic support. Teachers have limited access to training in foreign languages ​​or hospitality skills, which constrains their ability to prepare students for careers linked to tourism. Opportunities for students and universities remain narrow, as internships, vocational pathways, and collaborations with businesses are not yet well developed. Communities recognize tourism's potential to support education but express concern that benefits are concentrated in specific hubs, leaving many rural schools excluded. The study underscores the need for stronger linkages between tourism and education through targeted teacher training, structured internship programs, and equitable revenue-sharing mechanisms. By highlighting both opportunities and gaps, the research provides insights that can guide policymakers, educational institutions, and tourism stakeholders in designing more inclusive strategies. Ultimately, strengthening the connection between tourism and education can enhance human capital, promote equitable development, and contribute to Madagascar's long-term socio-economic progress.